Family involvement with the diabetes regimen in young people: the role of adolescent depressive symptoms. Issue 5 (7th March 2013) - Wu, Y. P.; Hilliard, M. E.; Rausch, J.; Dolan, L. M.; Hood, K. K.
Abstract Aims In young people with Type 1 diabetes, depressive symptoms and shared responsibility for management of diabetes impact upon diabetes management and control. However, the simultaneous effects of both depressive symptoms and parental involvement on diabetes self‐care and glycaemic control have not been examined. Thus, the aim of the current study was to examine the relationships between parental involvement and adolescent depressive symptoms in predicting blood glucose monitoring and glycaemic control. Methods One hundred and fifty young people with Type 1 diabetes (mean age 15.3 years) and their parents completed responsibility sharing and depressive symptom assessments, meter assessment of blood glucose monitoring and HbA1c at baseline and then 6, 12 and 18 months. Results Parental involvement affected HbA1c through blood glucose monitoring only at low levels of adolescent depressive symptoms (score ≤ 6), which made up only 20% of the sample. In the presence of more depressive symptoms, parental involvement no longer was related to HbA1c through blood glucose monitoring. This was the relationship in the majority of the sample (80%). Conclusions While most young people in this sample are not showing evidence of high levels of depressive symptoms, even modest levels of distress interfere with parental involvement in diabetes management. By addressing adolescent depressive symptoms, interventions promoting parental involvement in these families may be more effective.